Soils and olericultural practices in circumpolar region of Russia at present and in the past - Nizamutdinov, Timur; Suleymanov, Azamat; Morgun, Evgeniya; Yakkonen, Kirill; Abakumov, Evgeny (Frontiers in Sustainable Food Systems, 2022)
Circumpolar regions are often associated with activities such as reindeer herding, hunting, fishing, and gathering wild foods, but few know that locals have practiced olericulture since ancient times. Under a changing climate, the agricultural frontier will inevitably shift northward, so it is important to understand the current and past patterns of local soil functioning. Olericultural practices in the Arctic region seem difficult due to the harsh climate; however, it is being implemented. In this paper, we report the agricultural practices used by local residents to increase the yield of crops grown in the Yamal region. We also studied the chemical properties and fertility of soils under private gardens (both active and abandoned). At present, the yields of private olericulture in Yamal even exceed those of industrial vegetable-growing farms. It is revealed that private vegetable growers can achieve an increase in soil fertility by increasing the content of nutrients (P2O5 over 1,500 mg kg−1, K2O up to 500 mg kg−1) and organic carbon up to 17%, as well as the regulation of the acid-alkaline regime. It is also found that soil fertility indicators in private vegetable gardens are higher compared to industrial fields. Such soils are not typical for the cryolithozone and can be classified as Anthrosols. Soils of abandoned vegetable gardens can retain a high level of fertility for a long time due to the specific climatic conditions of the Arctic. As a result, the research showed that it is possible to grow vegetables beyond the Arctic Circle by adapting local soils and applying specific practices typical for cryolithozone.